Structure and kinetics of formation of APTS/GPTS-derived organic/inorganic hybrids - Awano, Carlos M. [UNESP]; Donatti, Dario A. [UNESP]; De Vicente, Fabio S. [UNESP]; Vollet, Dimas R. [UNESP] (American Chemical Society (ACS), 2013)
The structure and the kinetics of formation of APTS/GPTS-derived organic/inorganic hybrids were studied in situ by small-angle-X-ray scattering. The data were interpreted in terms of a process of primary particles formation and growth of mass-fractal clusters. At the very early stage, the population of the nonfractal primary particles (D = 3) increases with time. As the mass-fractal clusters appear (D < 3) as a result of the aggregation process, the radius of gyration, Rg, of the clusters increases on average. At advanced stages of aggregation, the clusters grow in a mechanism in which the number of particles per clusters increases while the number of clusters diminishes with time, in such a way that the correlation volume of the clusters, Vc, fulfills the relationship Vc â̂ R g D, in agreement with a mass-fractal character of the clusters. These results supporting a cluster-cluster aggregation process, together with the typically very low value found for the mass-fractal dimension D, are in favor of a diffusion-controlled cluster aggregation mechanism. © 2013 American Chemical Society.
Keywords: Aggregation process; Cluster aggregation; Cluster-cluster aggregation; Diffusion-controlled; Number of clusters; Organic/Inorganic hybrids; Primary particles; Radius of gyration; Fractal dimension; Agglomeration